Improving the physical properties of starch using a new kind of water dispersible nano-hybrid reinforcement. (20th August 2015) - Morales, Noé J.; Candal, Roberto; Famá, Lucía; Goyanes, Silvia; Rubiolo, Gerardo H.
Highlights: Composites of starch glycerol matrix with MWCNT–hercynite hybrid were developed. Low hybrid content significantly modified the properties of matrix. Addition of hybrid to the starch glycerol matrix increased the crystalline fraction. Young modulus, stress at break and toughness increased with hybrid content. Water vapor permeability decreased with hybrid content. Abstract: Plasticized cassava starch matrix composites reinforced by a multi-wall carbon nanotube (MWCNT)–hercynite (FeAl2 O4 ) nanomaterial were developed. The hybrid nanomaterial consists of FeAl2 O4 nanoparticles anchored strongly to the surface of the MWCNT. This nano-hybrid filler shows an irregular geometry, which provides a strong mechanical interlocking with the matrix, and excellent stability in water, ensuring a good dispersion in the starch matrix. The composite containing 0.04 wt.% of the nano-hybrid filler displays increments of 370% in the Young's modulus, 138% in tensile strength and 350% in tensile toughness and a 70% decrease in water vapor permeability relative to the matrix material. All of these significant improvements are explained in terms of the nano-hybrid filler homogenous dispersion and its high affinity with both plasticizers, glycerol and water, which induces crystallization without deterioration of the tensile toughness.